The Fohsella chronocline in middle Miocene sediments from the Ontong Java Plateau, Pacific Ocean - Adam R Eisenach; Daniel Clay Kelly (PANGAEA, 2006)
Micropaleontologists have traditionally recognized the mid-Miocene Fohsella lineage as a flagship for phyletic gradualism within the planktic foraminifera. However, study of a deep-sea record from the western equatorial Pacific (ODP Site 806) reveals that coiling ratios within this clade suddenly (<5 kyr) shift after a prolonged, ancestral state of near randomness (~50%) to a transient phase (13.42–13.43 Ma) of dextral dominance (~75%) immediately following the first common occurrence of keeled fohsellids. This brief period of dextral dominance was abruptly (<5 kyr) succeeded by an irreversible change to sinistral dominance (~96%). Fohsellid abundances decline markedly through the interval in which the sinistral preference is established. The shift to sinistrality (13.42 Ma) predated the deepening of fohsellid depth ecology by ~240–488 kyr, indicating that these two events were unrelated. This view is supported by a lack of delta 18O evidence for depth–habitat differences between the two chiral forms, which refutes the notion that sinistral fohsellids were “pre-adapted” for ensuing hydrographic change because they occupied a deeper depth habitat than their dextral counterparts. Planktic foraminiferal assemblages become strongly oligotrophic in character through the interval in which the fohsellid delta 18O increase is recorded, indicating that the migration to deeper depths was fostered by an expansion of the mixed layer in the western equatorial Pacific. Salient aspects of this brief, but conspicuous faunal change are a marked increase in the abundance of symbiont-bearing globigerinoidids, a concomitant collapse of local Jenkinsella mayeri/siakensis populations, and reduced fohsellid abundances. The rapid and permanent nature of the Fohsella sinistral shift provides a distinct, unequivocal datum that may prove useful for correlating mid-Miocene sections throughout the Caribbean Sea and tropical regions in the western sectors of the Pacific and Atlantic. The coiling ratio changes that occurred during the evolution of the Fohsella chronocline probably reflect changing population dynamics between cryptic genotypes with different coiling preferences.
Supplement to: Eisenach, AR; Kelly, DC (2006): Coiling preferences and evolution in the middle Miocene Fohsella chronocline. Marine Micropaleontology, 60(4), 243-257, https://doi.org/10.1016/j.marmicro.2006.05.001